EVALUASI PELAKSANAAN PROGRAM KELUARGA HARAPAN DALAM MENGATASI KEMISKINAN DI KECAMATAN LAWA KABUPATEN MUNA BARAT - Suriyani BB; La Ode Agus Said; Rifal; Usman (Halu Oleo University, 2025)
This study aims to evaluate the implementation of the Family Hope Program in overcoming poverty in Lawa District, West Muna Regency. The research method used is descriptive qualitative, with data collection techniques using observation, interviews, and documentation. The results of the study showed that the Evaluation of the implementation of the Family Hope Program in Lawa District, West Muna Regency, showed Effectiveness. The Family Hope Program has been effective in improving the welfare of underprivileged families, especially in the education, health, and economic sectors. However, more intensive assistance is still needed to overcome existing participation obstacles. Efficiency, this program runs efficiently with good coordination between related parties and timely distribution. However, there are still technical obstacles, such as data errors, that need to be corrected.